Level Of Awareness Regarding Eye Donation Among Patients Attending Eye OPD At Tertiary Hospital - Khan, Nida; Agrawal, Prakash Chand; Tigga, Marry; Saini, V. K.; Gupta, Saroj (National Journal of Community Medicine, 2015)
Introduction: Ocular trauma and corneal ulceration are signifi- cant causes of corneal blindness. India needs 2.5 lakh donated eyes every year but able to collect a maximum of just 25,000 eyes Aim of the study was to evaluate the level of awareness regarding eye donation among OPD patients at a tertiary hospital. Method: We recorded 154 patients presenting to the out-patient department of a tertiary care hospital who were willing to partic- ipate in the survey were requested to fill the form and answer 11 questions pertaining to awareness of eye donation. The questions had multiple options and subjects were requested to answer as per their choice. Result: The results showed that 14% responders were not aware about eye donation. Awareness through eye donation campaign was maximum (38%) followed by awareness through mass media (18%). 60% responders were not aware about any eye bank in Madhya Pradesh. 47% responders were not aware that only de- ceased can donate eyes and not living individuals. 79% respond- ers were not aware that filling of eye donation form by the indi- vidual during lifetime is not mandatory for eye donation. 50% responders were aware that only corneal diseases can be cured by corneal transplantation. Conclusion: There is gross lack of awareness about eye donation among outpatient department and their relatives.